Evaluation of Road Damage Using The Pavement Condition Index (PCI) Method on Jalan Raya Waringin, Palasah District, Majalengka Regency - Dina Natalia; Andri Irfan Rifa'i (LEADER: Civil Engineering and Architecture Journal, 2023)
Evaluation of road damage is an important process in monitoring and maintaining existing road infrastructure. The Pavement Condition Index (PCI) method is an approach that is commonly used to measure road conditions and identify the level of existing damage. Evaluation will be focused on the Jalan Raya Waringin section, to be precise in Palasah District, Majalengka Regency. This section will be selected based on its relevance, accessibility, and representation of overall road conditions in the area. The evaluation aims to assess road damage on Jalan Raya Waringin using the PCI method to get an overview of the condition of the road infrastructure. The assessment will help identify the extent and type of existing road damage Jalan Raya Waringin is a one-way road, with a width of 3.8 meters. From the results of the research data collection, it was obtained several types of damage occurred on the 250 m long section of Jalan Raya Waringin. Starting from the front of the Riyadul Huda Foundation to the front of the Adila motorbike (workshop), there is several damage such as Alligator Cracking, Potholes with a moderate level of damage (medium), and others. The results of the research on the condition of the Jalan Raya Waringin section, Palasah District, Majalengka Regency using the PCI method obtained an overall 47.8%. PCI Fair, meaning that the condition of the road pavement is quite significant and requires periodic maintenance. The types of damage that can be found in Jalan Raya Waringin, Palasah District, Majalengka Regency include Holes, Weathering and Loose Grain, Crocodile Skin Cracks, Longitudinal and Transverse Cracks, and Subsidence. Damages that occur as a result of subgrade soil conditions or unfavorable foundations. Weathering and Lose Grain, Crocodile Skin Cracks, Longitudinal and Transverse Cracks, and Collapse. Damages that occur as a result of subgrade soil conditions or unfavorable foundations.